Determining pitch-angle diffusion coefficients from test particle simulations - A. Ivascenko; S. Lange; F. Spanier; R. Vainio (Institute of Physics Publishing, Inc., 2025)
Transport and acceleration of charged particles in turbulent media is a topic of great interest in space physics and interstellar astrophysics. These processes are dominated by the scattering of particles off magnetic irregularities. The scattering process itself is usually described by small-angle scattering with the pitch-angle coefficient D μμ   playing a major role. Since the diffusion coefficient D μμ   can be determined analytically only for the approximation of quasi-linear theory, the determination of this coefficient from numerical simulations has, therefore, become more important. So far these simulations yield particle tracks for small-scale scattering, which can then be interpreted using the running diffusion coefficients. This method has a limited range of validity. This paper presents two new methods that allow for the calculation of the pitch-angle diffusion coefficient from numerical simulations. These methods no longer analyse particle trajectories, but the change of particle distribution functions. It is shown that they provide better resolved results and allow for the analysis of strong turbulence. The application of these methods to Monte Carlo simulations of particle scattering and hybrid MHD-particle simulations is presented. Both analysis methods are able to recover the diffusion coefficients used as input for the Monte Carlo simulations and provide better results in MHD simulations especially for stronger turbulence.